Structure, emplacement mechanism and magma-flow significance of igneous fingers – Implications for sill emplacement in sedimentary basins - Galland, Olivier (2019)
Field and seismic observations show that numerous sills exhibit lobate morphologies. Each lobe corresponds to a distinct igneous segment exhibiting a finger-like shape, the long axis of which is commonly interpreted as a magma-flow indicator. Robust understanding of the emplacement mechanisms of finger-shaped sills, and direct observations supporting finger orientation as magma-flow indicator are lacking. In this paper, we present the results of detailed structural mapping on an exceptional, easily accessible 1-km long outcrop in the Neuquén Basin, Argentina, that exhibits a sill, its contacts and the structures in the finely layered sedimentary host rock. We show that the sill is made of distinct segments that grew, inflated or coalesced. We also demonstrate that the fingers were emplaced according to the viscoelastic fingering or viscous indenter models, with no field evidence of tensile elastic fracture mechanism as commonly assumed in mechanical models of sill emplacement. We identified new structural criteria at the intrusion's contacts for inferring magma flow direction during the magma emplacement. Our small-scale structural observations carried out on a seismic-scale outcrop have the potential to considerably aid the structural interpretation of seismic data imaging igneous sills, i.e. to fill the standard gap between outcrop-scale field observations and seismic-scale geophysical data.